2015
DOI: 10.1039/c5ce00402k
|View full text |Cite
|
Sign up to set email alerts
|

The racemate-to-homochiral approach to crystal engineering via chiral symmetry breaking

Abstract: CrystEngComm HIGHLIGHTGuangming Li et al.The racemate-to-homochiral approach to crystal engineering via chiral symmetry breaking VolumeThe racemate-to-homochiral approach is a method to transform or separate a racemic mixture into homochiral compounds. This protocol, if without an external chiral source, is categorized into chiral symmetry breaking. The resolution processes without chiral induction are highly important for the investigation of the origin of homochirality in life, pharmaceutical synthesis, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…On the other hand, the introduction of secondary auxiliary ligands, such as carboxylic acids, has also been attempted . Progresses in the synthetic and functional aspects of chiral metal–organic frameworks containing only achiral building blocks have been reviewed recently. ,,, …”
Section: Chiral Supramolecular Assemblies From Achiral Building Blocksmentioning
confidence: 99%
“…On the other hand, the introduction of secondary auxiliary ligands, such as carboxylic acids, has also been attempted . Progresses in the synthetic and functional aspects of chiral metal–organic frameworks containing only achiral building blocks have been reviewed recently. ,,, …”
Section: Chiral Supramolecular Assemblies From Achiral Building Blocksmentioning
confidence: 99%
“…The chiral crystallization of an achiral compound is of great interest in terms of the generation of optical activity simply by crystallization, and chiral crystals have been used as chiral precursors in asymmetric synthesis and are associated with the origin of life. We have previously reported that some aromatic amides, aromatic sulfonamides, , and a benzene-1,3,5-tricarboxylic acid derivative show chiral crystallization phenomena. This type of crystallization, however, does not occur very frequently: only 5–10% of achiral compounds can be crystallized as chiral crystals, and the mechanism of the crystallization is still unknown. However, several groups of compounds with common skeletons, including aromatic sulfonamides (4 of 12 compounds), S -aryl 2-benzoylbenzothionates (3 of 7 compounds), simple benzophenone derivatives (13 of 55 compounds), and 1,3-indanedione derivatives (11 of 54 compounds) have been found to show chiral crystallization in higher proportions in comparison to other achiral compounds.…”
Section: Introductionmentioning
confidence: 99%
“…An et al suggest that racemic mixtures condense on the substrate in three different ways: (a) a racemic compound in which both enantiomers are present in the same single crystal, (b) a conglomerate in which a single crystal contains only one enantiomer, but the sample as a whole is racemic, and (c) a solid solution, in which the film contains both enantiomers, but there is no orderly structure. 30 Because no orderly structure can be seen in Figure 2A, we suggest that noncrystallized racemic BINOL condenses in a solid solution shortly after evaporation. During the crystallization process, the regular structure in the sample greatly increases.…”
Section: Morphology Of the Racemic Binol Filmsmentioning
confidence: 81%
“…It is of great interest for our work to contemplate whether the crystallites in a racemic BINOL sample consist of only one type of enantiomers (homochiral) or both (heterochiral). An et al suggest that racemic mixtures condense on the substrate in three different ways: (a) a racemic compound in which both enantiomers are present in the same single crystal, (b) a conglomerate in which a single crystal contains only one enantiomer, but the sample as a whole is racemic, and (c) a solid solution, in which the film contains both enantiomers, but there is no orderly structure 30 . Because no orderly structure can be seen in Figure 2A, we suggest that noncrystallized racemic BINOL condenses in a solid solution shortly after evaporation.…”
Section: Resultsmentioning
confidence: 99%